An empirical study of the effects of personality in pair programming using the five-factor model - Salleh, Norsaremah; Mendes, Amelia; Grundy, John; Burch, Giles St. J (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
Pair Programming (PP) has been long researched in industry and academia. Although research evidence about its usefulness is somewhat inconclusive, previous studies showed that its use in an academic environment can benefit students in programming and design courses. In our study, we investigated the ldquohumanrdquo aspect of PP; in particular the effects that personality attributes may have on PP's effectiveness as a pedagogical tool. We conducted a formal experiment at the University of Auckland to investigate the influence of personality differences among paired students using the five-factor model as a personality measurement framework. The aim of our study was to improve the implementation of PP as a pedagogical tool through understanding the impact the variation in the personality profile of paired students has towards their academic performance. Our findings showed that differences in personality traits did not significantly affect the academic performance of students who pair programmed.